Small Molecule Approaches for Promoting Neurogenesis - Longo, Frank M.; Yang, Tao; Xie, Youmei; Massa, Stephen M. (Current Alzheimer Research, 2006)
The discovery of small molecules capable of promoting neurogenesis will contribute to the elucidation of the physiological roles of neurogenesis and to novel therapeutic approaches. Small molecule development can be targeted to the promotion of precursor proliferation, survival, migration or maturation and might be applied to augmenting physiological neurogenesis already present in the dentate gyrus or subventricular zone/olfactory bulb or to normally nonneurogenic regions relevant to neuropathological states. Current small molecule discovery can be assessed from the perspective of the following categories: compounds modulating physiological signaling pathways regulating neurogenesis including the sonic hedgehog, bone morphogenic protein Wnt/,-catenin, Notch and chemokine systems; growth factor mimetics; protein tyrosine phosphatase inhibitors; existing drugs including antidepressants, lithium, valproate, sidenafil and statins; hormones, steroids and peptides; and neurotransmitter receptor agonists and antagonists. Unbiased, high throughput screening will likely lead to the discovery of additional active compounds and the recognition of novel mechanisms regulating neurogenesis. A major therapeutic challenge will consist of the identification of molecular targets and mechanisms relatively specific for precursor cells of interest.
Keywords: Alzheimer' s disease